Coupled explicit-damping simulation of laser shock peening on x12Cr steam turbine blades. Issue 1 (February 2021) - Fameso, Festus; Desai, Dawood; Kok, Schalk; Newby, Mark; Glaser, Daniel
Abstract: Timeous prevention of, and recovery from, downtimes due to in-service failure of crucial power plant components, like turbine blades, portends huge consequences in the form of operational and financial viability concerns. Intensive research and development in manufacturing, re-manufacturing and condition-based maintenance of these components have birthed a novel technique, which deploys high intensity lasers to induce compressive residual stresses to the surface of the blades. This paper presents the application of an alternate computational modelling technique in simulating this surface treatment technique on X12Cr steel, an exotic steam turbine blades material, while also investigating the economic parameters of the induced residual stresses. A numerical model is developed in this work using the commercial finite elements software ABAQUS©. The results show this computational modelling technique as being time efficient. The parametric outcomes of the simulation agreed with experimental results, lending credence to its validity. Induced compressive stresses as high as 700 MPa and depths close to 1 mm from the surface of the blade were obtained. This by indication can prospectively quell crack initiation, growth and unplanned failure of the blade while in service, with the introduced simulation technique offering a solution for timely, non-destructive mechanical integrity enhancement of engineered components.